LEGITIEME PORTIE DALAM HUKUM WARIS ISLAM DI INDONESIA - Puspita, Shintiya Dwi; Fadhly, Fabian (Faculty of Law, Parahyangan Chatolic University, 2015)
Indonesia recognizes three different inheritance system based respectively on the Civil Code, Islamic law and adat law. This article discusses the regulation concerning legitieme portie, the absolute right of the successor (heirs) which by law cannot be disregarded by the benefactor. The question here is whether legitieme portie, expressly regulated in the western inheritance law may also be found in the Islamic inheritance system? The second question concerns the possibility of â within the Islamic inheritance system â through the application of the legitieme portie - to deny the wife and/or parentsâ right to the inheritance. This research argues that the Islamic inheritance system contains rules which cannot be disregarded by the benefactor and at the same time guarantee the wifeâs right to the inheritance left by the benefactor.